Climate-Fungal Pathogen Modeling Predicts Loss of Up to One-Third of Tea Growing Areas - Tibpromma, Saowaluck; Dong, Yang; Ranjitkar, Sailesh; Schaefer, Douglas A.; Karunarathna, Samantha C.; Hyde, Kevin D.; Jayawardena, Ruvishika S.; Manawasinghe, Ishara S.; Bebber, Daniel P.; Promputtha, Itthayakorn; Xu, Jianchu; Mortimer, Peter E.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Climate change will affect numerous crops in the future; however, perennial crops, such as tea, are particularly vulnerable. Climate change will also strongly influence fungal pathogens. Here, we predict how future climatic conditions will impact tea and its associated pathogens. We collected data on the three most important fungal pathogens of tea (Colletotrichum acutatum, Co. camelliae, and Exobasidium vexans) and then modeled distributions of tea and these fungal pathogens using current and projected climates. The models show that baseline tea-growing areas will become unsuitable for Camellia sinensis var. sinensis (15 to 32% loss) and C. sinensis var. assamica (32 to 34% loss) by 2050. Although new areas will become more suitable for tea cultivation, existing and potentially new fungal pathogens will present challenges in these areas, and they are already under other land-use regimes. In addition, future climatic scenarios suitable range of fungal species and tea suitable cultivation (respectively in CSS and CSA) growing areas are Co. acutatum (44.30%; 31.05%), Co. camelliae (13.10%; 10.70%), and E. vexans (10.20%; 11.90%). Protecting global tea cultivation requires innovative approaches that consider fungal genomics as part and parcel of plant pathology.